Reflections on Integral and Integrated Heritage Care at the Threshold of the Third Millennium - Marc Laenen (Ochrona Dziedzictwa Kulturowego)
Our living environments are being affected by climate change, increased migrations, aggression due to political conflicts and by new real estate developments which cause new challenges to their cultural heritage resources. The “reflection” attempts to promote an integral and integrated approach for cultural heritage enhancement, integral because all heritage sectors should join forces and integrated in planning following an agreed vision on man and society, guided by the principles of sustainability and standards of quality. Especially the problem of integration of different cultures in an agreed “consociation” is being analysed. Three paths of strategic action are suggested to create the right environment for such approach: a strong advocacy and educational strategy with convincing arguments as an answer to the “why” question, a methodology to implement UNESCO’s HUL Recommendation as an answer to the “how” question and a system of interpretation and presentation of cultural heritage as a basis for mutual understanding, respect  leading to comparative heritage understanding. The “reflection” is intended to initiate discussions.